1993
DOI: 10.1007/bf01658705
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis: A continuing problem in the neonate

Abstract: Necrotizing enterocolitis (NEC) is a syndrome of diverse etiologies with a significant mortality rate affecting mostly prematurely born stressed infants. Now recognized as a discrete entity, it had been poorly defined because other conditions seem to represent the same entity. A number of risk factors have been identified that appear to "trigger" NEC, though these have been questioned because they have been present just as frequently in premature and older infants who did not develop NEC as in those that did. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 100 publications
0
6
1
1
Order By: Relevance
“…We could not confirm the relation between polycythemia and NEC described in other investigations [2,3,13]. There arc sev eral possible mechanisms for cocaine-induced gastrointestinal ischemia, but a definite cau sal relation between fetal cocaine exposure and NEC is still uncertain [14][15][16], In this study no differences were found in maternal drug exposure among the NEC and the con trol group.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…We could not confirm the relation between polycythemia and NEC described in other investigations [2,3,13]. There arc sev eral possible mechanisms for cocaine-induced gastrointestinal ischemia, but a definite cau sal relation between fetal cocaine exposure and NEC is still uncertain [14][15][16], In this study no differences were found in maternal drug exposure among the NEC and the con trol group.…”
Section: Discussioncontrasting
confidence: 56%
“…Several investigators have pointed out the role of infectious agents as possible factors in the development of NEC [1,8,9,16]. The pathology of NEC is consistent with the inter action of epithelial cells with bacterial toxins [17], There is a long list of organisms that have been related to NEC, but no specific bac teria or virus has been associated with most of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar de ainda não haver consenso sobre a unicausalidade no seu desenvolvimento [1,2,8,9], o nascimento prematuro tem sido citado como o principal fator de risco para a ECN [1][2][3][4][5][6][7][8][9][10][11], acrescido da isquemia, presença de bactérias patogênicas e substrato metabólico no trato gastrointestinal. Tais fatores agindo simultaneamente no intestino imaturo do recém-nascido pré-termo (RNPT) têm sido reconhecidos pelos neonatologistas como pré-requisitos para o desenvolvimento da ECN há mais de 50 anos [1,2,10,12].…”
Section: Introductionunclassified